Cochlear implants before 9 months of age led to more natural spoken language development without increased surgical risks. (10th September 2019) - Karltorp, Eva; Eklöf, Martin; Östlund, Elisabet; Asp, Filip; Tideholm, Bo; Löfkvist, Ulrika
Abstract: Aim: Evidence suggests that cochlear implants are beneficial for language development, but there is no consensus about the ideal age for surgery. We investigated how language development and surgical safety were affected by patients' ages. Methods: This study comprised 103 children (52 boys) aged 4.3‐16 years who received cochlear implants at 5‐29 months at the Karolinska University Hospital, Stockholm, Sweden, between 2002 and 2013. All showed typical development and were from monolingual homes. Bilateral implants were common (95%). The children were regularly assessed on language understanding, vocabulary and speech recognition by a multi‐disciplinary team for 10.0 ± 3.7 (4.7‐16.0) years. Results: There were no associations between complications after surgery and the age when children had their first implant. Children implanted at 5‐11 months reached an age‐equivalent level of language understanding and better vocabulary outcome sooner than subgroups implanted later. Children who had surgery at 12‐29 months demonstrated more atypical and delayed language abilities over time. Early implantation, preferably before 9 months, may lead to a more typical trajectory of spoken language development. Conclusion: Our findings showed that cochlear implantation before 9 months was safe. Early implantation may reduce the negative effects of auditory deprivation and promotes more natural and synchronised language development. Abstract :